Biaya Produksi, Biaya Penjualan, Daya Beli dan Laba Bersih pada Perusahaan Manufaktur Periode 2020 - Murni Salfadilla Saepudin; Darya Setia Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research aims to determine the effect of production costs and sales costs on purchasing power and net income in manufacturing companies listed on the Indonesia Stock Exchange for the period 2020. The research method used is quantitative methods with descriptive and associative approaches, where the type of data used is secondary data from financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the 2020 period and the value of the Consumer Price Index (CPI) and Producer Price Index (PPI) as indicators of purchasing power. The total population in this study amounted to 195 manufacturing companies. The sampling technique used is purposive sampling technique, from these results obtained a sample of 36 manufacturing companies with a period of 4 quarters during 2020 so that the number of samples used is 144 samples. The data analysis method used in this study is multiple regression analysis method with path analysis model using the help of the IBM SPSS 26 application. Based on the t test, it is known that in equation one partially production costs have a positive effect on purchasing power and sales costs have a negative effect to purchasing power. While in equation two, production costs have a negative effect on net income, while sales costs and purchasing power have no effect on net income. The results of the path analysis show that purchasing power is not an intervening variable or there is no mediating effect between the relationship between production costs and selling costs on net income.